2017
DOI: 10.1002/j.1681-4835.2017.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Digital Archive System to Develop Digitally Resilient Youths in Marginalised Communities in South Africa

Abstract: Promoting digital skills among the youth in marginalised communities can boost their digital resilience, facilitate effective participation in the knowledge economy and foster positive development. However, in developing countries, government and other stakeholders are confronted by several challenges that hamper such projects. These include poor digital infrastructure, a lack of digital capacity, high levels of digital illiteracy, limited access to local digital content, and widespread apathy and mistrust amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In addition, the excessive time spent on digital platforms is a big risk that can cause significant mental health distress to students, which can impact an individual’s lifestyle such as their sleep schedule or appetite ( 28 ). Several studies also showed that understanding unhealthy online threats is an important start in building digital resilience ( 4 , 16 , 26 ). Users were encouraged to report harm when using online technologies, which was a style of proactive self-efficacy to reflect their capability to discern risks during online experiences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the excessive time spent on digital platforms is a big risk that can cause significant mental health distress to students, which can impact an individual’s lifestyle such as their sleep schedule or appetite ( 28 ). Several studies also showed that understanding unhealthy online threats is an important start in building digital resilience ( 4 , 16 , 26 ). Users were encouraged to report harm when using online technologies, which was a style of proactive self-efficacy to reflect their capability to discern risks during online experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Students with access to digital resiliency attributes at the time of stress or threat during the use of technology period have more chances to deal with these stressors in a positive way ( 26 , 34 ). Multiple studies showed that digital resilience had various positive impacts on psychological and social functioning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experience is an important element of project development, since the implementation of any project is surrounded by uncertainties, which are likely to have a negative impact to a project if they are not handled properly (Oeij, 2017). Evidence shows that experienced ICT experts are better suited in attaining various organizational goals, and even in showing their commitment to their projects (Ochieng et al, 2017). This is because, experience enhances the resilience of an expert, amid challenging circumstances.…”
Section: Null Hypothesis One the Technical Competency Of Ict Experts ...mentioning
confidence: 99%
“…However, there is no clear understanding of how such agglutination will facilitate learning in a virtual environment. Previous authors have argued that computer mediated peer learning within a virtual environment can help promote student development and create positive outcomes (Khalili & Olugbara, 2011) as in the case of digital media archive systems (Ochieng, Olugbara & Marks, 2017).…”
Section: Constructivism Theories For Online Teachingmentioning
confidence: 99%